A new species of Panus (Panaceae, Polyporales) from Paraíba, Brazil - Galvão, Vitória Ingrid P.; Koroiva, Ricardo; Wartchow, Felipe (Phytotaxa, 2023)
Panus is the type genus of the family Panaceae. Here, we describe P. paraibensis, a new conspicuous species collected in the northeastern region of Brazil, intending to contribute to the knowledge of species richness in the mentioned area. It is characterized by the cream-white to pale pink basidiomes with a villose margin, a short laterally inserted stipe covered by strigose-villose projections, thin-walled pleurocystidia that sometimes arise deep in the subhymenium and project briefly above the level of the other hymenial elements, small basidiospores, and versiform cheilocystidia. It can be treated morphologically close to Asiatic P. kinabaluensis and P. johorensis, which primarily differ in the aspects of the hymenial cystidia.